A male patient with proptosis and palatal perforation: A diagnostic challenge - Peyman Mottaghi; Sam Mirfendereski; Farshad Riahi; Shahin Rajaeih (Radiology Case Reports)
Granulomatosis with polyangiitis (Wegener's granulomatosis), affects many systems and can show up in a variety of ways. Sometimes, only a few organs are affected. Rare complications of this vasculitis syndrome include a retroorbital pseudotumor with proptosis due to chronic tissue inflammation, as well as necrosis with subsequent palate perforation. We present a 59-year-old male who had multiple ophthalmologic evaluations for chronic pain, redness, and proptosis in the right eye. During the workup for eye problems, he underwent surgery for chronic right nasal obstruction and bloody discharge. After 2 weeks, he noticed pain and ulceration in his hard palate that rapidly transformed into a perforation of the palate and was finally referred to a rheumatologist due to increased erythrocyte sedimentation rate. A CT scan was requested for the patient, which showed an orbital mass and palatal perforation. A biopsy of the mass behind the eye showed that it was inflamed across the membrane and had fibrinoid necrosis, which is a sign of necrotizing vasculitis.